2011
DOI: 10.1073/pnas.1114152108
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and functional analysis of galactooligosaccharide uptake bylacSinLactobacillus acidophilus

Abstract: Probiotic microbes rely on their ability to survive in the gastrointestinal tract, adhere to mucosal surfaces, and metabolize available energy sources from dietary compounds, including prebiotics. Genome sequencing projects have proposed models for understanding prebiotic catabolism, but mechanisms remain to be elucidated for many prebiotic substrates. Although β-galactooligosaccharides (GOS) are documented prebiotic compounds, little is known about their utilization by lactobacilli. This study aimed to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 55 publications
6
93
1
Order By: Relevance
“…ANOVA analysis and Tukey tests were performed to identify statistically significant differences in relative abundance between time points. *P < 0.05. glycolytic enzyme essential for GOS metabolism that typically is genetically linked with a LacS permease responsible for transport and internalization of GOS (6). B. dentium has been less thoroughly characterized, is mostly associated with the oral cavity, and recently was shown to be increased in the stools of 100-to 108-y-old centenarians living in Bama, Guangxi (China) as compared with younger (80-to 99-y-old) elderly persons (19).…”
Section: Discussionmentioning
confidence: 99%
“…ANOVA analysis and Tukey tests were performed to identify statistically significant differences in relative abundance between time points. *P < 0.05. glycolytic enzyme essential for GOS metabolism that typically is genetically linked with a LacS permease responsible for transport and internalization of GOS (6). B. dentium has been less thoroughly characterized, is mostly associated with the oral cavity, and recently was shown to be increased in the stools of 100-to 108-y-old centenarians living in Bama, Guangxi (China) as compared with younger (80-to 99-y-old) elderly persons (19).…”
Section: Discussionmentioning
confidence: 99%
“…26,35) It seems plausible that GOS-induced bifidobacteria utilize this system for GOS uptake, because it does not require ATP for substrate import and thus allows energy-efficient and rapid adaptive transport. Recently, Andersen et al clearly demonstrated by generating a lacS-deficient mutant of Lactobacillus acidophilus that LacS is indispensable for GOS uptake by bacteria; this also supports the strong link between LacS and …”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] Accordingly, we embarked on a search for a "GOS operon" in bifidobacteria. We chose B. adolescentis YIT 4011 T as a model bacterium, because (as indicated above) it exhibited highly adaptable use of GOS.…”
Section: Gos-induced Operon Of B Adolescentis Yit 4011 Tmentioning
confidence: 99%
“…Genes successfully deleted using this gene replacement strategy in L. acidophilus NCFM include surfacelayer (S-layer) protein X, (LBA0512), aggregation promoting factor (LBA0493), myosin cross-reactive antigen (LBA0649), and lactose permease (LBA1463). 15,[20][21][22] Establishing this system in L. gasseri provides numerous advantages, notably the ability to positively select for excision recombinants yielding gene deletions or replacements. In concurrent efforts, this system was used to successfully and efficiently delete the sortase A gene (srtA) from L. gasseri (Call et al, submitted).…”
Section: Discussionmentioning
confidence: 99%